Dynamic testing of free field response in stratified granular deposits. Issue 84 (May 2016) - Dihoru, L.; Bhattacharya, S.; Moccia, F.; Simonelli, A.L.; Taylor, C.A.; Mylonakis, G.
Abstract: The dynamic free field response of two stratified deposits with different stiffness ratios between the top and the bottom layer was analysed by shaking table testing. The granular deposits were contained in a laminar shear box and subjected to a wide set of dynamic inputs with different frequency content. Two exploratory modal testing techniques were employed to measure the natural frequency of the individual layers and the results were employed in the calculation of the fundamental period of the overall stratified profile by an extended variant of the Madera procedure[1] . The dynamic response was investigated in relation to the frequency content of the dynamic excitation, the granular material properties and the stiffness characteristics of the enclosing container. The measured dynamic stiffness for the mono-layered and the bi-layered sand deposits compare well with previous empirical curves for sands increasing the confidence in the shaking table and shear stack testing as tools of dynamic investigation of granular media. Highlights: Experimental results concerning the dynamics of stratified granular deposits. Modal testing techniques for natural frequency measurement on the shaking table. Method to evaluate the equivalent fundamental periods of stratified deposits. Shear strain-stress behaviour analysis in relation to a wide set of seismic inputs. Influence of granular material properties on dynamic response of layered soils.